Membrane-Active Antibacterial Agents Based on Calix[4]arene Derivatives: Synthesis and Biological Evaluation - Fang, Shanfang; Dang, Yuan-Ye; Li, Haizhou; Li, Hongxia; Liu, Jiayong; Zhong, Rongcui; Chen, Yongzhi; Liu, Shouping; Lin, Shuimu (Frontiers in Chemistry, 2022)
Bacteria have developed increasing resistance to currently used antimicrobial agents. New classes of antimicrobial drugs are urgently required to fight drug-resistant pathogens. Here, we designed and synthesized a series of calix[4]arene derivatives as antibacterial agents by biomimicking the structural properties and biological functions of antibacterial peptides. After introducing cationic hydrophilic moieties and preliminary structural optimization, we obtained a lead compound (16) that exhibited excellent antibacterial activity against Gram-positive bacteria, low toxicity toward mammalian cells and poor hemolytic activity. The antibacterial mechanism studies showed that compound 16 can destroy bacterial cell membrane directly, leading to bacterial death and a low tendency to develop bacterial resistance.